CYBERSECURITY AS A FACTOR IN THE DEVELOPMENT OF THE DIGITAL ECONOMY - J. Konopleva; V. Korystov; D. Teslenko (Вестник Северо-Кавказского федерального университета)
In this article there are discussed the theoretical foundations of the digital economy and the features of its functioning in Russia. Also here is outlined the role of blockchain as a fundamental basis of cybersecurity. Within the framework of the State Program «Digital Economy of the Russian Federation}}, the expected items of expenditure for the implementation of tasks under the section ((Information Security} are analyzed. Also here the directions of the Program, aimed to develop the cybersecurity, namely the support of domestic software developers, are separately given with ranking on the high cost of implementation and with the indication of the responsible Ministries, Funds and Centers. There is an emphasis, placed on the need to promote the standard of cyber insurance.